2011
DOI: 10.1186/bcr3073
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of breast cancer metastasis by Runx2 and estrogen signaling: the role of SNAI2

Abstract: IntroductionIn contrast to its role in breast cancer (BCa) initiation, estrogen signaling has a protective effect in later stages, where estrogen receptor (ER)α loss associates with aggressive metastatic disease. We asked whether the beneficial effect of estrogen signaling in late-stage BCa is attributable to the recently reported estrogen-mediated antagonism of the pro-metastatic transcription factor Runx2.MethodsMCF7/Rx2dox breast cancer cells were engineered with a lentivirus expressing Runx2 in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 57 publications
(102 reference statements)
7
118
0
1
Order By: Relevance
“…In addition, a growing number of miRs have been revealed as signatures for different diseases including cancers (46 -48). Although miR-218 functions as a tumor-suppressive "oncomiRNA" to suppress certain cancers (49,50), elevated miR-218 expression has also previously been associated with estrogen receptor positive breast tumors indicating a possible role in certain breast cancer phenotypes (51,52). Consistent with latter findings, miR-218 promotes metastasis-related molecular properties in MDA-MB-231 aggressive breast cancer cells.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, a growing number of miRs have been revealed as signatures for different diseases including cancers (46 -48). Although miR-218 functions as a tumor-suppressive "oncomiRNA" to suppress certain cancers (49,50), elevated miR-218 expression has also previously been associated with estrogen receptor positive breast tumors indicating a possible role in certain breast cancer phenotypes (51,52). Consistent with latter findings, miR-218 promotes metastasis-related molecular properties in MDA-MB-231 aggressive breast cancer cells.…”
Section: Discussionsupporting
confidence: 77%
“…miR-218 was reported to function as a tumor suppressor through regulation of the Slit-Robo pathway in some cancers, but not others (49). The Slit2 gene harboring miR-218 is expressed in metastatic breast cancer cells and is associated with metastasis to brain, but not to bone (50), whereas both Wnt signaling and estrogen are linked to bone metastasis (22,52). These results suggest that the expression of the two forms of miR-218 arising from its host genes serve different biological functions than their host genes in osteoblasts and breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of RUNX2 is negatively correlated with ERα expression, and this has been implicated as a mechanism by which ERα promotes maintenance of a differentiated epithelial phenotype by antagonising the EMT-inducing effect of RUNX2 [158]. Transplantation of Runx2-/-mouse mammary buds into immunocompromised recipient mouse fat pads demonstrated that RUNX2 is not required for mammary outgrowth but Runx2-/-outgrowths exhibit defective alveologenesis during late pregnancy (>18 days post coitum- [157]).…”
Section: Runx Transcription Factorsmentioning
confidence: 98%
“…RUNX2, best known for its roles in skeletal development (13, 14), has also been implicated in carcinogenesis, including the promotion of breast and prostate cancer metastasis (8, 1520). RUNX2 activity in PCa is negatively regulated by PTEN through a FOXO1-dependent mechanism (21), RUNX2 expression progressively increases during PCa development in the PTEN conditional knockout mouse model (22) and its immunoreactivity is higher in human PCa than in prostatic intraepithelial neoplasia (PIN) and normal prostate epithelium (16, 23, 24).…”
Section: Introductionmentioning
confidence: 99%